The use of soil-rock mixtures in dams in Portugal - Caldeira, L. (2010)
Soil-rock mixtures are being used in the construction of dam shells. The measured deformations associated to these materials have been larger than expected. This situation represents new challenges to compaction techniques and their control as well as to the determination of the characteristics of the embankment that results from the compaction method, as those characteristics suffer important changes according to the relative percentage of the existing fractions. For the execution control of the soil-rock mixtures from the Odelouca dam borrow areas, a series of vibratory compaction tests and standard compaction tests were performed to estimate reference values for the maximum dry density and optimum water content of these materials. Odelouca dam is a zoned embankment dam, 76 m high, with clayey soil at the core and weath-ered schist with a significant fraction of oversized particles at the shells. The results of the compaction control, as well as its behaviour during the construc-tion phase, are herein presented.